1996
DOI: 10.1108/eb029022
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Downsizing in an Enterprise with Job Security

Abstract: This paper comprises a theoretical study of factors influencing the utility of organisational downsizing. Companies downsize in order to adapt to lower demand or as a means to improving efficiency, i e to improve their performance/cost ratio. With perfect information and no legal or ethical restrictions, management would remove employees with the lowest utility. This information is normally lacking and downsizing is instead based on a headcount or on total salary cost reduction. The efficiency of such measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The HRCA literature is replete with models for estimating the currency-valued payoff from HRM investments (e.g., Boudreau, 1991;Mabon, 1996;Klaas & McClendon, 1996), which begin with HRM programs such as compensation, staffing, training, turnover control, etc.…”
Section: The Purpose: Enhancing Key Stakeholder Reactions and Decisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HRCA literature is replete with models for estimating the currency-valued payoff from HRM investments (e.g., Boudreau, 1991;Mabon, 1996;Klaas & McClendon, 1996), which begin with HRM programs such as compensation, staffing, training, turnover control, etc.…”
Section: The Purpose: Enhancing Key Stakeholder Reactions and Decisionsmentioning
confidence: 99%
“…It is suggested that the significant and increasing difference between the financial book value and market capitalization value of corporations is due to the growing importance of things not measured by the financial book value, requiring new statements reflecting intellectual capital or intangibles. Leading organizations such as DuPont and Skandia have implemented such systems, adding even more new measures to a field already struggling to apply systems such as human resource accounting, behavioral costing, human resource costing, competencybased inventories, and a host of other measurement systems.The HRCA literature is replete with models for estimating the currency-valued payoff from HRM investments (e.g., Boudreau, 1991;Mabon, 1996; Klaas & McClendon, 1996), which begin with HRM programs such as compensation, staffing, training, turnover control, etc. , 1994;Carson, Becker & Henderson, 1998).…”
mentioning
confidence: 99%
“…Review 28,1/2 92 1986; Hunter and Schmidt, 1982;Mabon, 1996;Martin and Raju, 1992). Most of the literature has dealt with personnel selection problems.…”
Section: Personnelmentioning
confidence: 99%
“…If an organization adopts programs only if they enhance the return on capital invested, however, the return on other resources (e.g., land, transportation assets, human capital) may not be optimized. For example, capital-based returns may be maximized by large layoffs because of significant labor cost savings, perhaps enhancing short-run return on capital; however, if the actual constraint is on human capital, layoffs designed merely to cut costs may exacerbate the unseen human capital constraint, causing long-term performance problems (Mabon, 1996;Milkovich & Boudreau, 1997).…”
Section: How Capital Became Keymentioning
confidence: 99%